Transcriptional Targeting of Mature Dendritic Cells with Adenoviral Vectors via a Modular Promoter System for Antigen Expression and Functional Manipulation - Ilka Knippertz; Andrea Deinzer; Jan Dörrie; Niels Schaft; Dirk M. Nettelbeck; Alexander Steinkasserer (Journal of Immunology Research)
To specifically target dendritic cells (DCs) to simultaneously express different therapeutic transgenes for inducing immune responses against tumors, we used a combined promoter system of adenoviral vectors. We selected a 216 bp short Hsp70B′ core promoter induced by a mutated, constitutively active heat shock factor (mHSF) 1 to drive strong gene expression of therapeutic transgenes MelanA, BclxL, and IL-12p70 in HeLa cells, as well as in mature DCs (mDCs). As this involves overexpressing mHSF1, we first evaluated the resulting effects on DCs regarding upregulation of heat shock proteins and maturation markers, toxicity, cytokine profile, and capacity to induce antigen-specific CD8+ T cells. Second, we generated the two-vector-based “modular promoter” system, where one vector contains the mHSF1 under the control of the human CD83 promoter, which is specifically active only in DCs and after maturation. mHSF1, in turn, activates the Hsp70B′ core promotor-driven expression of transgenes MelanA and IL-12p70 in the DC-like cell line XS52 and in human mature and hence immunogenic DCs, but not in tolerogenic immature DCs. These in vitro experiments provide the basis for an in vivo targeting of mature DCs for the expression of multiple transgenes. Therefore, this modular promoter system represents a promising tool for future DC-based immunotherapies in vivo.